2001
DOI: 10.1039/b109355j
|View full text |Cite
|
Sign up to set email alerts
|

Determination of liposome/water partition coefficients of organic acids and bases by solid-phase microextraction

Abstract: The extraction of two methylated anilines and three chlorinated phenols by solid-phase microextraction (SPME) fibers coated with polyacrylate was investigated as a function of pH. Only the neutral species of the acids and bases partitioned into the polymer. Extraction kinetics were accelerated for the hydrophobic phenols at pH values around their acidity constant. This is presumably due to a reconstitution of the neutral species in the unstirred aqueous layer adjacent to the polymer surface by the charged spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…With a molecular weight of human albumin of 65 kDa [19], this corresponds to 1.0 ± 0.1 pmol of HSA per fibre. Thus, fouling of the fibre by protein adsorption does take place, as reported by Poon et al [20,21] and suggested by Escher et al [22]. According to Heringa et al [9], fouling could have two types of effects on the uptake of compounds into the fibre coating: either the fouling blocks uptake or the adsorbed protein adds to the measured amount of compound by its bound ligands.…”
Section: Competitive Elisamentioning
confidence: 78%
“…With a molecular weight of human albumin of 65 kDa [19], this corresponds to 1.0 ± 0.1 pmol of HSA per fibre. Thus, fouling of the fibre by protein adsorption does take place, as reported by Poon et al [20,21] and suggested by Escher et al [22]. According to Heringa et al [9], fouling could have two types of effects on the uptake of compounds into the fibre coating: either the fouling blocks uptake or the adsorbed protein adds to the measured amount of compound by its bound ligands.…”
Section: Competitive Elisamentioning
confidence: 78%
“…The PAH sorption coefficient between matrix and aqueous solution (K matrix ) at each matrix concentration can be calculated from Eq. (3), which was modified from Escher et al (2002),…”
Section: Influences Of Different Matrices On the C Free Of Pahs And Mmentioning
confidence: 99%
“…As can be seen, the normalization to neutral BPA has no significant change to the profiles. In SPME it is generally assumed that only the neutral species is partitioning into the fiber (Escher et al, 2002) or at least the portioning of the charged species is less than 10% of the neutral species (Lutzhoft et al, 2000). Therefore, the D value of BPA should be constant as BPA (a weak acid with reported pK a = 9.60-10.2) should be present mainly as nondissociated form in the studied pH range of 5.0-8.5.…”
Section: Influence Of Salinity and Phmentioning
confidence: 99%
“…Schwarzenbach and co-workers investigated the partition in liposome-water system of a series of substituted phenols and anilines with pH dependent results (Escher and Schwarzenbach, 1996;Escher et al, 2002) and Arnold et al also found that the association of triorganotin compounds with dissolved humic acids was strongly pH dependent (Arnold et al, 1998). A few studies on the association of chlorophenols with various DOM were reported.…”
Section: Introductionmentioning
confidence: 99%